Association of a SNP in KISS 1 gene with reproductive traits in goats. Issue 6 (3rd July 2021) - Sahoo, Siddhant Sekhar; Mishra, Chinmoy; Kaushik, Rakesh; Rout, Pramod Kumar; Singh, Manoj Kumar; Bhusan, Saket; Dige, Mahesh Shivanand
ABSTRACT: The native goat genetic resources of India proved to have immense genetic potential for sustainable development. Improving the reproductive traits of the goat will be economically beneficial to the livestock owners. In the current research work genetic variability in KiSS1 gene was explored and its association with the reproductive traits were studied. A novel polymorphism (G231C) was identified in the promoter region of KiSS1 gene with statistical significant ( P < 0.05) association with the litter size in goats. However, any such association of SNP with age at sexual maturity, age at first breeding and kidding interval could not be observed. Statistical significant effect of breed on reproductive traits was also observed. Due to this SNP, a change in transcription factor binding site was predicted which may have significant effect on reproductive traits. Nucleotide sequence analysis of KiSS1 gene revealed a close sequence homology within the goat species.